Oocytes Skipped Spawning Through Atresia Is Regulated by Somatic Cells Revealed by Transcriptome Analysis in Pampus argenteus - Yang, Yang; Wang, Guohao; Li, Yaya; Hu, Jiabao; Wang, Yajun; Tao, Zhen (Frontiers in Marine Science, 2022)
In teleost, follicle atresia is a common degenerative process that can occur at different stages of ovarian development. In this study, we depicted the cellular morphology of silver pomfret (Pampus argenteus) follicular atresia in detail and divided it into four different stages from Aα to Aδ stages based on the main cellular characteristics. High-throughput RNA sequencing was used to profile follicle atresia from Aα to Aδ stages, and many stage-specific genes were identified. In early atretic ovary, a great number of genes in cytokine-cytokine receptor interaction were obviously downregulated, suggesting that somatic cells might directly induce the follicle atresia by disrupting the normal conservation with germ cells. Meanwhile, the regulatory network of immune cell–related pathways was discovered in the process of atresia. The genes enriched in Th cell differentiation, leukocyte transendothelial migration, cholesterol metabolism, and so on were abundantly expressed, indicating that the immune cells play key roles in the process of in follicle atresia. Moreover, a model was proposed to illustrate how somatic cells mediate the process of follicle atresia. The study provides important insights into the molecular networks underlying follicle atresia in teleost.